Disitamab vedotin combined with pyrotinib as salvage treatment in Her-2-amplified treatment refractory metastatic colorectal cancer: a case report - Chen, Jianxin; Wang, Jian; Zheng, Qinhong (Frontiers in Pharmacology, 2025)
BackgroundHuman epidermal growth factor receptor 2 (HER-2) amplification has been identified in approximately 3% of patients with metastatic colorectal cancer (mCRC). Owing to the lack of established anti-ERBB2 therapeutic approaches, mCRC patients with Her-2 amplification rarely receive targeted treatments. Moreover, conventional chemotherapy regimens are not ideal for these patients, leaving options in the advanced stage limited to best supportive care or participation in clinical drug trials.Case presentationThis report presents a case of a patient with Her-2-amplified refractory mCRC treated with a salvage regimen combining Disitamab Vedotin and Pyrotinib, resulting in a partial response and progression-free survival for 6 months, which is still ongoing.ConclusionThis case study suggests that the anti-Her-2 regimen involving Disitamab Vedotin and Pyrotinib may offer a potential salvage treatment option for patients with Her-2-amplified mCRC patients. However, further validation in larger cohorts is necessary in future studies.